北极黄河站邻近湖泊沉积物有机碳同位素记录及其气候信息 - 何建华; 余雯; 陈立奇; 门武 (2012)
2007年7月和8月,在北极黄河站站区的2个湖泊采集沉积柱两支(1号柱样:78°56.489′n,11°49.194′E;2号柱样:78°56.554′n,11°51.576′E),采用210 Pb定年法测定了2个沉积物柱样的沉积速率,同时对两个柱样中有机碳同位素δ13 C垂直分布进行了分析。结果表明:1)沉积物柱样的沉积速率分别为1.05MM/A和0.91MM/A;2)两个柱样的δ13 C随深度的变化趋势基本一致,随时间的延长呈现出“降低-增加-降低-增加-降低“的趋势;3)北极黄河站的气温在近300年间呈现出“降低-升高-降低-升高-降低“的交替过程。 Arctic is favored by researchers due to its sensitivity and feedback to Global Climate Change,and the organic δ13C record of lake sediment is a key indicator for the environmental climate change.The sedimentary rates and δ13C of two sediment cores(No.1 and No.2),collected from two lakes near the Arctic Yellow River Station of China during July to Aug of 2007,were determined in order to investigate the climate change of the Arctic during the past centuries.The sedimentary rates,determined with 210Pb method,of sample No.1 and sample No.2 were 1.05 mm/a and 0.91 mm/a,respectively,and the vertical distribution of organic δ13C of two sediment cores have similar trends during the same period.The results show that the temperature at the Arctic Yellow River Station of China during the last three centuries was unsteady,and was alternating with a "lower-higher-lower" process. 中国极地科学战略研究基金“黄河站邻近湖泊沉积物中有机碳同位素研究及其古气候环境意义初探”(20070221)